First observation of fouling of externally attached radio transmitters in an African river - Francois Jakob Jacobs; Olaf Lawrence Friedrich Weyl; Eva Marita Ulvan; Clinton Hay; Tor Fredrik Naesje (Water SA, 2020)
Fouling of externally attached tags is an important consideration in long-term tagging studies as it may affect fish behaviour and well-being. Two externally attached radio transmitters on African tigerfish Hydrocynus vittatus were covered with short green algae, after the fish were recaptured 49 and 64 days after tagging in the Kavango River, Namibia. This is the first observation of fouling on external radio transmitters from any African river which highlights the importance of conducting studies that evaluate the various health or behavioural effects resulting from tagging.